Surface display of Lys0859, a Streptococcus suis prophage lysin, on Bacillus subtilis spores and its antibacterial activity against Streptococcus suis - Linkang Wang; Linkang Wang; Linkang Wang; Xiaochao Duan; Xiaochao Duan; Xiaochao Duan; Xiaochao Duan; Mengyuan Zhu; Mengyuan Zhu; Mengyuan Zhu; Haiyan Wang; Haiyan Wang; et al. (Frontiers in Microbiology)
IntroductionStreptococcus suis, an important zoonotic and opportunistic pathogen in pigs, brings huge economic losses to the pig-raising industry and infects humans with diseases. Phage lysin is regarded as a promising substitute for antibiotics due to its ability to quickly and efficiently kill bacteria without easily developing resistance. However, their clinical applications have been hindered by inherent instability under environmental stressors.MethodsWe constructed B. subtilis spores displaying bacteriophage lysin Lys0859 using spore coat protein CotG as an anchoring motif. Environmental tolerance was evaluated through thermal (37–95°C), pH (1.0–8.0), and enzymatic challenges, while antibacterial efficacy against S. suis was assessed using agar diffusion assays and murine infection models with systemic bacterial load quantification.ResultsThe spore-display system enhanced environmental resistance of Lys0859 while preserving its bactericidal efficacy. In vitro assays demonstrated 1 × 106 CFU rBSCotG-0859 spores exhibited equivalent bactericidal activity to 39.11 μg free Lys0859 against S. suis. In vivo, spore treatment reduced S. suis SC19 colonization by 0.47–1.96 log units (p < 0.05) across all tissues compared with PBS controls.DiscussionThis study achieved functional display of prophage lysin Lys0859 on B. subtilis spores through CotG anchoring, demonstrating potent in vitro anti-streptococcal activity. Crucially, this strategy streamlined bioproduction by eliminating purification demands and lowering costs, lays the foundation for the clinical application of prophage lysin.